Neurocognitive consequences of occupational heavy metal exposure among electronic waste sorting workers in Thailand - Harasarn, Kornwika; Keawkaen, Practhaya; Thetkathuek, Anamai (Narra Sains Indonesia, 2026)
Electronic waste sorting workers in Thailand are chronically exposed to heavy metals, including lead (Pb), cadmium (Cd), and nickel (Ni), in informal work settings characterized by limited use of personal protective equipment and suboptimal hygiene practices. This study aimed to evaluate the associations between heavy metal exposure, individual risk factors, and neuropsychological performance among workers. A cross-sectional study was conducted involving 76 exposed workers and 49 non-exposed controls. Data were collected using structured interviews, surface wipe sampling of workplace dust for Pb, Cd, and Ni, and blood metal measurements. Neuropsychological function was assessed using the Digit Span Forward Test (DSFT) and Digit Span Backward Test (DSBT). The mean ages of the exposed and non-exposed groups were 47.39±12.64 and 49.92±8.46 years, respectively. Surface dust concentrations of Pb, Cd, and Ni were significantly higher in the exposed group than in controls (all p<0.001). In contrast, blood metal concentrations did not differ between groups (Pb: 6.41±1.49 vs 6.41±1.62µg/dL, p=0.885; Cd: 0.97±0.39 vs 0.91±0.28µg/L, p=0.501; Ni: 2.60±0.48 vs 2.52±0.45µg/L, p=0.689). No significant difference was observed in DSFT scores between groups (p=0.912). However, DSBT scores differed significantly (p<0.001), with the exposed group scoring higher (2.23±0.55) than the non-exposed group (1.72±0.39). Among exposed workers, simple linear regression identified education (β=0.353, p=0.002), income (β=0.257, p=0.025), age (β=-0.236, p=0.041), and alcohol consumption (β=-0.231, p=0.044) as significant predictors of DSFT performance. However, DSBT scores differed significantly (p<0.001). Drinking alcohol, smoking, Pb in dust, and working area size were significant predictors of DSBT performance (p=0.020, 0.022, 0.013, and <0.001, respectively). These findings indicate that cognitive performance among Thai informal e-waste workers is more strongly influenced by socioeconomic factors and surface lead contamination than by blood metal levels. Interventions focusing on education, income support, and routine workplace surface cleaning, supported by surface-based environmental monitoring and community health volunteers, are critical for protecting cognitive health in this vulnerable population.